Toledo Blade Pictorial. (Toledo-Ohio, 1835)
The Blade, also known as the Toledo Blade, is a newspaper in Toledo, Ohio published daily online and printed Thursday and Sunday by Block Communications. The newspaper was first published on December 19, 1835. (wikipedia)
Https://www.toledoblade.com
Engels
Krant, nieuwsbulletin